Accommodation of East African Rifting Across the Turkana Depression. Issue 2 (1st March 2020) - Knappe, E.; Bendick, R.; Ebinger, C.; Birhanu, Y.; Lewi, E.; Floyd, M.; King, R.; Kianji, G.; Mariita, N.; Temtime, T.; Waktola, B.; Deresse, B.; et al.
Abstract: Geodetic observations in the Turkana Depression of southern Ethiopia and northern Kenya constrain the kinematic relay of extension from a single rift in Ethiopia to parallel rifts in Kenya and Uganda. Global Position System stations in the region record approximately 4.7 mm/year of total eastward extension, consistent with the ITRF14 Euler pole for Nubia‐Somalia angular velocity. Extension is partitioned into high strain rates on localized structures and lower strain rates in areas of elevated topography, as across the Ethiopian Plateau. Where high topography is absent, extension is relayed between the Main Ethiopian Rift and the Eastern Rift across the Turkana Depression exclusively through localized extension on and immediately east of Lake Turkana (up to 0.2 microstrain/year across Lake Turkana). The observed scaling and location of active extension in the Turkana Depression are inconsistent with mechanical models predicting distributed stretching due to either inherited lithospheric weakness or reactivated structures oblique to the present‐day extension direction. Plain Language Summary: The continent of Africa is breaking up into multiple pieces. This divergence is accommodated through extension along the East African Rift System. The Turkana Depression, which lies on the border of Ethiopia and Kenya, is of interest due to its previous rifting episodes, low elevation compared to the surrounding rift system, and location linking more prominent rift valleys to the north and south. Global Position System observations of surface velocities show that extension in the Turkana Depression is confined to a narrow region, not distributed across a broad area. These results suggest the East African Rift System is accommodating the breakup of the African continent through a combination of distributed deformation in areas with high topography and localized extension across low elevation rift basins. Key Points: The Turkana Depression accommodates divergence through localized extension African extension is accommodated by a combination of high and low strain rates Topographic gradients appear to influence the style of extension throughout the African rift system